Metabolic interactions between axons and Schwann cells of the mouse sciatic nerve - Rich, Laura (2022)
Astrocytes of the central nervous system (CNS) provide glycogen derived lactate to axons when energy substrate availability is low and when axons have an increased energy demand. Signals, including glutamate and K+, released from axons communicate the need for metabolic support and trigger astrocyte lactate production. Whether similar metabolic interactions occur between axons and Schwann cells of the peripheral nervous system (PNS) is less well understood. The association of peripheral neuropathy with the metabolic disease diabetes makes the study of axon-Schwann cell metabolic interactions valuable. Myelinating Schwann cells possess glycogen and glycolytically metabolise this to lactate, which their associated axons, known as A fibres, benefit from as an energy substrate when glucose availability is reduced. The aim of this thesis was to use the mouse sciatic nerve to investigate the role of Schwann cells in providing lactate to A fibres during increased axonal activity and the ability of K+ to act as a metabolic signal. Fructose metabolism of the mouse sciatic nerve was also investigated.